(3EKHGJ GdThGQO eeG hLO aj MhGTi GdcJH ef GdahGFOs
(3ChdgG (B:s
(3GdMeO ddg Ydi fYe dG jMUjgG GdYOO hUdi Gddg Ydi CTQa ef NOeg GdSYO hYdi Bdg hUMHg eG JHSe HQb s
(3BNQgG (B:s
(3GdHGA hGdLje hGdMGA hLejY GdMQha hGdeYfi GdCda eKd GdhGMO adgPG SejfGg cJGH GdCda hbO fLR GdZQV ef gPG GdcJGH hGdMeO ddg GdYGdejf Bejf Je s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdChbGa GdYGeI (B_ (3HZOGO (B(226) s
Keywords: (3GdeYGQa GdYGeIs